Development of functional literacy in secondary education: thematic discourse analysis (Journal of Educational Sciences, 2022)
Functional literacy development is an important part of secondary education in Kazakhstan which is reflected in the state educational programmes for education and science development in 2012, 2016, 2020. This area has been studied by researchers, policy makers and teachers in Kazakhstan. However, the concepts of functional literacy and the development of related basic/key competencies are constantly changing and expanding. Therefore, there is a need for a literature review which introduces the various perspectives on functional literacy development in secondary education with major themes and developments. This article presents the main results of the thematic discourse analysis which is focused on the latest functional literacy related publications. The analysis employed the following methods: bibliographical synthesis of literacy and topic modelling LDA (Latent Dirichlet Allocation). This article presents the results of the topic modelling analysis which contributes to the discussion in the area of functional literacy development at national and international levels. It also introduces major areas of development including methods and approaches in functional literacy education and assessment. This paper might contribute to the work of policy makers, researchers, secondary school teachers and those who are interested in functional literacy development and education in Kazakhstan and abroad.Key words: functional literacy, secondary school, thematic discourse analysis.